The Role of Family Support in the Self-Confidence of Young People - Besarta Sadriu; Zenel Orhani; Emrush Thaci (European Scientific Journal, ESJ, 2026)
Introduction: Family support is a critical factor in the psychological and emotional development of young people. It fosters self-confidence through emotional support, encouragement, and a sense of security. This study examines the influence of adolescents’ perceptions of family relationships on their self-evaluation and overall self-confidence. Methods: The study included 54 participants aged 18–25. Data were collected using a structured, anonymous questionnaire measuring family support and self-confidence. The questionnaire was pilot-tested, revised, and demonstrated high reliability (Cronbach’s Alpha = 0.89 for 8 items). Descriptive statistics, correlation analysis, and t-tests were used to analyze the data. Results: Participants reported a high level of perceived family support (M = 34.61, SD = 6.20). Most respondents strongly agreed that their families provide emotional support, encouragement, and good communication. A significant positive correlation was found between family support and self-confidence (r = 0.672, p < 0.01). No significant gender differences were observed. All hypotheses were confirmed, indicating that family support positively influences self-confidence, self-esteem, and psychological well-being. Conclusion: The findings highlight the family as a key protective and supportive factor in youth development. Promoting positive family relationships strengthens adolescents’ self-confidence and emotional well-being. These results can inform psycho-educational interventions and strategies to support young people in both family and educational contexts.